Papel do resveratrol sobra a modulação do receptor Aril-hidrocarboneto (AhR) e o desenvolvimento da próstata de ratos expostos ao 2, 3, 7, 8-tetraclorodibenzo-p-dioxina (TDCC) durante a gestação - Silveira, Lívia Teresa Ribeiro da [UNESP] (2015)
TCDD (2,3,7,8-tetrachlorodibenzo-p-dioxin) is the most toxic environmental contaminant which mechanism of action is through the interaction with the aryl hydrocarbon receptor (AhR). In the prostate, TCDD works inhibiting the prostatic budding and activating the AhR-dependent pathways. Resveratrol is known by your anticancer, antiplatelet, anti-inflammatory and anti-allergic properties, besides acting as AhR antagonist. Therefore, the current research aimed to assess the protective effect of Resveratrol on prostate development in rats exposed to TCDD during early prostate morphogenesis. Pregnant Wistar rars were divided in four experimental groups: Control, TCDD. TCDD+Resveratrol and Resveratrol. TCDD (1μg/kg body weight) diluted in corn oil was administered by gavage as a single dose on 15th gestational day (GD15) while Resveratrol (20mg/kg body weight) was given by gavage (diluted in 8% of ethanol) between GD10 and postnatal day 21 (PND21). Newborn males (PND1) were euthanized to evaluate immediate effects of TCDD and Resveratrol on the initial prostatic morphogenesis, through morphological and immunohistochemical assays, while male rats (PND90) were euthanized for evaluation the late effects. There was decreasing of prostatic buds number in TCDD group. In the same group, basal cells showed weak immunoreactivity for p63 when compared to Control and TCDD+Resveratrol. TCDD reduced the cell proliferation index in the epithelial buds and mesenchyme as well as the number of androgen receptor (AR)-positive mesenchyme cells compared to Control and TCDD+Resveratrol groups. It is worth mentioning that the AR immunostaining was weak in the epithelial buds and intense in the surrounding mesenchyme in all experimental groups. On the other hand, α-actin staining was less intense in the differentiated mesenchymal cell that surrounded the epithelial buds in the TCDD group. Regarding to adult animals (PND90), the histological analysis revealed in ...